The Effect of Prior Knowledge on Student Performance in an Accounting Course: Causal Effect or Moderating Effect? - Helen Shun-mun WONG; Carmen Ka-man SUM; Alvin Yau-tak WONG (Communications of International Proceedings, 2021)
This paper proposes to study the effect of prior knowledge on students’ academic performance. Prior knowledge has been found to have a causal or bivariate relationship with academic performance, but this finding has not yet been confirmed in some studies. It has been argued that this relationship is not simple and linear. Prior knowledge may carry a moderating effect on student performance. We propose to explore its moderating effect and then compare its magnitude with its causal effect on students’ academic performance. Two structural models are proposed while student effort and mathematics background are included as the antecedents.
Keywords: Prior Knowledge; Accounting Education; Student Performance